Estimating the respiratory syncytial virus-associated hospitalisation burden in older adults in European countries: a systematic analysis - Tiantian Zhang; Rachel M. Reeves; Shihao Ma; Yumeng Miao; Shiqi Sun; Alejandro Orrico-Sánchez; Marcus Panning; Arantxa Urchueguía-Fornes; Danielle Vuichard-Gysin; Harish Nair; Maria João Fonseca; Alen Marijam; et al. (BMC Medicine)
Abstract Background With respiratory syncytial virus vaccines recently approved for use among older adults, country-level respiratory syncytial virus (RSV) disease burden estimates are needed to inform local RSV immunisation strategy. We aimed to estimate country-level RSV hospitalisation burden in older adults in Europe. Methods We compiled data on RSV hospitalisation burden in adults aged ≥ 60 years in Europe from published studies (systematic review: PROSPERO CRD42024516945), surveillance data, and unpublished data from international collaborators. We adjusted for diagnostic testing, clinical specimens, and case definitions through statistical modelling techniques and generated country-level hospitalisation rate estimates; for countries with no available data, we developed an ensemble model to predict RSV hospitalisation rates. We also estimated RSV in-hospital case fatality ratio (hCFR) for countries with available data. Results We included 14 studies (3 unpublished studies). The adjusted RSV-associated hospitalisation rates were overall 2.2 to 6.4 times higher than unadjusted estimates. Among 5 countries with available data, adjusted annual RSV hospitalisation rates ranged from 193/100,000 person-years in the Netherlands (95% confidence interval [CI]: 125–304) and Finland (141–274) to 414/100,000 in Denmark (322–514). The RSV hospitalisation rates predicted by the ensemble model in 23 additional countries ranged from 223/100,000 to 317/100,000 person-years. RSV hCFR ranged from 6.73% (4.63–9.69) in Spain to 10.14% (4.91–19.79) in Switzerland. Conclusions This study addresses knowledge gaps in RSV hospitalisation burden among older adults in Europe while highlighting the importance of adjusting for RSV case under-ascertainment. These findings might be relevant for country’s considerations of RSV immunisation strategies for older adults. Graphical Abstract